Analisis Kualitas Empiris Butir Soalujian Pendidikan Agama Kristen SD Inpres Palsatu Berbasis Outcome Based Education - Merti Tana; Sefanya Merah Loinati (Indo Publishing, 2026)
This study aims to analyze the empirical quality of Christian Religious Education (CRE) exam items at SD Inpres Palsatu based on Outcome-Based Education through difficulty level and discrimination index. This research used a descriptive quantitative approach with 27 student answer sheets as subjects and 20 multiple-choice items as objects. Data analysis was performed using Microsoft Excel 2021. The results showed that all items had a moderate difficulty level (P=0.37–0.67). For discrimination indices, 85% of the items were categorized as good and very good (D≥0.40), while 15% were categorized as sufficient (D=0.20–0.39) and need revision. Overall, 17 items (85%) were declared feasible to be accepted without revision, and 3 items need to be revised. It is concluded that the developed test instrument has good quality and can be used to measure learning outcomes in CRE. Future research is recommended to complete the analysis of distractor effectiveness.